(untitled) (Ágora Journal, 2025)
Understanding the law in Portuguese America, a legal space marked by a plurality of sources and jurisdictions, implies looking beyond the secular justice and analyzing other judicial spaces such as the Catholic Church’s. Among these forums were the episcopal courts that existed in each diocese with an extensive criminal jurisdiction, whose practices are still poorly understood. Seeking to fill this gap, this article explores the exercise of ecclesiastical criminal jurisdiction in the city of São Paulo, from the installation of its episcopal court in 1747 until 1800, a period marked by strong changes in relations between the Church and the power of the Crown. As sources, the 237 criminal cases processed in the ecclesiastical auditorium during the period were consulted, as well as theological-legal literature and political communications sent to the Overseas Council. The article concludes that the bishop’s criminal jurisdiction continued to be relevant and recognized by the Crown until the turn of the century, but underwent strong theoretical changes linking its power to the King, which manifested themselves in local disputes between the bishop and the ordinary judge of São Paulo and, possibly, in the reduction of cases judged, despite the low reliability of the available documents for quantitative analysis.